Mechanisms of estrogen influence on skeletal muscle: mass, regeneration, and mitochondrial function - Pellegrino, A.; Tiidus, P. M.; Vandenboom, R. (Sports Medicine, 2022)
Human menopause is widely associated with impaired skeletal muscle quality and significant metabolic dysfunction. These observations pose significant challenges to the quality of life and mobility of the aging population, and are of relevance when considering the significantly greater losses in muscle mass and force-generating capacity of muscle from post-menopausal females relative to age-matched males. In this regard, the influence of estrogen on skeletal muscle has become evident across human, animal, and cell-based studies. Beneficial effects of estrogen have become apparent in mitigation of muscle injury and enhanced post-damage repair via various mechanisms, including prophylactic effects on muscle satellite cell number and function, as well as membrane stability and potential antioxidant influences following injury, exercise, and/or mitochondrial stress. In addition to estrogen replacement in otherwise deficient states, exercise has been found to serve as a means of augmenting and/or mimicking the effects of estrogen on skeletal muscle function in recent literature. Detailed mechanisms behind the estrogenic effect on muscle mass, strength, as well as the injury response are beginning to be elucidated and point to estrogen-mediated molecular cross talk amongst signalling pathways, such as apoptotic signaling, contractile protein modifications, including myosin regulatory light chain phosphorylation, and the maintenance of muscle satellite cells. This review discusses current understandings and highlights new insights regarding the role of estrogen in skeletal muscle, with particular regard to muscle mass, mitochondrial function, the response to muscle damage, and the potential implications for human physiology and mobility.